1994
DOI: 10.1073/pnas.91.16.7807
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring active N-domain of human angiotensin I-converting enzyme.

Abstract: Angiotensin I-converting enzyme (ACE, kininase II) is a single-chain protein containing two active site domains (named N-and C-domains according to position in the chain). ACE is bound to plasma membranes by its C-terminal hydrophobic transmembrane anchor. Deal fluid, rich in ACE activity, obtained from patients after surgical colectomy was used as the source. Column chromatography, including modified affinity chromatography on lisinopril-Sepharose, yielded homogeneous ACE after only a 45-fold purification. N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 43 publications
2
76
0
2
Order By: Relevance
“…38 When we compared the forms from WKY rats and ACE BN-1, with 190 kDa and BN-2, with 65 kDa, the data indicated that different strains presented the same enzyme forms. At this time, we can conclude that the ACE form of 80 kDa is present only in the genetically hypertensive strains and may be a genetic marker of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…38 When we compared the forms from WKY rats and ACE BN-1, with 190 kDa and BN-2, with 65 kDa, the data indicated that different strains presented the same enzyme forms. At this time, we can conclude that the ACE form of 80 kDa is present only in the genetically hypertensive strains and may be a genetic marker of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the amount of unhydrolyzed substrate and the increase in hydrolysis products [Ang-(1-5), BK-(1-7), and BK-(1-5)] were determined by comparison of the peak areas with peak areas of known standard peptides 31 in HPLC. The results of the hydrolysis of Ang-(1-7) and BK by N-ACE and C-ACE are given in Table 1.…”
Section: Hydrolysis Of Ang-(1-7) and Bk By N-ace And C-acementioning
confidence: 99%
“…31 N-ACE was purified from ileal fluid collected after colostomy with the collaboration of N. Davidson of the University of Chicago, somatic ACE from human cadaver kidneys, and C-ACE from rabbit testicles obtained from Pel-Freez Co. Approval for human tissue studies was granted by the Institutional Review Board at the University of Chicago and for animal tissue study by the Animal Care and Usage Committee at the University of Illinois at Chicago.…”
Section: Enzyme Purificationmentioning
confidence: 99%
“…The same nACE enzymes were obtained by Marques et al (2003) in the urine of Wistar-Kyoto and Spontaneously Hypertensive rats (SHR), and by Ronchi et al (2005) in different tissues of SHR, suggesting that the 90/80 kDa ACE could be a possible biological marker of hypertension (Marques et al;2005). Moreover, Deddish et al (1994) described an active soluble form of nACE in human ileal fluid, with a molecular mass of 108 kDa, thereby differing from the enzymes described in human urine (Deddish et al;1994).…”
Section: Angiotensin I-converting Enzyme (Ace)mentioning
confidence: 76%